Clinical prognosticators and targets in the immune microenvironment of intrahepatic cholangiocarcinoma - Lozzi, Isis; Arnold, Alexander; Barone, Matthias; Johnson, Juliette Claire; Sinn, Bruno V; Eschrich, Johannes; Gebert, Pimrapat; Wang, Ruonan; Hu, Mengwen; Feldbrügge, Linda; Schirmeier, Anja; Reutzel-Selke, Anja; et al. (Oncoimmunology, 2024)
The tumor immune microenvironment (TIME) plays a critical role in the immune response In many cancers, including intrahepatic cholangiocarcinoma (ICC). Molecular subtyping of the ICC microenvironment already revealed inter-tumoral heterogeneity with variant profiles of immune cell infiltrates. A recent study created an in-depth immune cell atlas of the TIME in biliary tract cancers and could demonstrate the relevance of specific immune cell subpopulations on patient outcome. We are able to provide a distinctive characterization of TIME, separating tumor epithelial- and stroma areas, in a large and representative ICC cohort using digitalized image analysis on tissue microarrays (TMA) as well as multiplex imaging mass cytometry (IMC). The study was designed for identification of immune cell prognosticators allocating institutional ICC patients into a discovery (2008-15) and a validation (2010-19) cohort. Immune cell subpopulations were correlated with clinicopathological characteristics and patient outcome. Our results highlight: i. The important role of CD4+ T cell infiltration in ICC patients; ii. ICC tumors with high density of immune cells associated with PD-L1 expression identifies a subset of patients with variant tumor biology; iii. Stimulation of STAT1 pathway may be a relevant target to turn "cold" into "hot" tumors. Intrahepatic cholangiocarcinoma (ICC) is a disease with poor prognosis and limited therapeutic options. We investigated the tumor immune microenvironment (TIME) to identify predictors of disease outcome and to explore targets for therapeutic modulation. Liver tissue samples were collected during 2008-2019 from patients (n = 139) diagnosed with ICC who underwent curative intent surgery without neoadjuvant chemotherapy. Samples from the discovery cohort (n = 86) were immunohistochemically analyzed on tissue microarrays (TMAs) for the expression of CD68, CD3, CD4, CD8, Foxp3, PD-L1, STAT1, and p-STAT1 in tumor core and stroma areas. Results were digitally analyzed using QuPath software and correlated with clinicopathological characteristics. For validation of TIME-related biomarkers, we performed multiplex imaging mass cytometry (IMC) in a validation cohort (n = 53). CD68+ cells were the predominant immune cell type in the TIME of ICC. CD4+ high T cell density correlated with better overall survival (OS). Prediction modeling together with validation cohort confirmed relevance of CD4+ cells, PD-L1 expression by immune cells in the stroma and N-stage on overall disease outcome. In turn, IMC analyses revealed that silent CD3+CD4+ clusters inversely impacted survival. Among annotated immune cell clusters, PD-L1 was most relevantly expressed by CD4+FoxP3+ cells. A subset of tumors with high density of immune cells ("hot" cluster) correlated with PD-L1 expression and could identify a group of candidates for immune checkpoint inhibition (ICI). Ultimately, higher levels of STAT1 expression were associated with higher lymphocyte infiltration and PD-L1 expression. These results highlight the importance of CD4+ T cells in immune response against ICC. Secondly, a subset of tumors with "hot" TIME represents potential candidates for ICI, while stimulation of STAT1 pathway could be a potential target to turn "cold" into "hot" TIME in ICC.